Phytochemicals and antioxidant activities of twelve edible wild plants from Eastern Anatolia, Turkey - ALACA,Kevser (2022)
Abstract Wild edible plants are important nutrient contributors in the diet of populations both in rural and urban areas. Eastern Anatolia has high plant diversity, and many plants are widely used as traditional food and medicine. In this study, approximate compositions, bioactive compounds and antioxidant capacities of twelve edible wild plants in Eastern Anatolia were investigated. L-ascorbic acid, total chlorophyll, total carotenoid and total phenolic contents of analyzed edible wild plants ranged from 1.03 to 10589.71 mg/kg dw, 88.70 to 1740.02 mg/kg dw, 25.00 to 700.20 mg β-car. eq./kg dw, and 444.14 to 2071.96 mg GA eq./kg dw, respectively. Chlorogenic and gallic acids were the most abundant phenolic acids in the plant samples. Rutin, quarcetin, kaempferol and luteolin were identified and quantified in the samples. Luteolin (15.98- 832.82 mg/kg dw) was identified in almost all tested plants (except Coriandrum sativum). The results showed that Arum conophalloides, Rumex tuberosus, Rheum ribes, Plantago lanceolata, Tragopogon longirostris, and Chenopodium album had high contents of different phytochemicals, and antioxidant activities. These plants are available for a short time of the year and in small quantities. Future studies should be focused on biological, functional and toxicological assays and finally for commercial production of these promising plants.